2023
DOI: 10.1039/d3gc02028b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the selectivity of visible light-driven hydroxylation of benzene to phenol by using Cu, Fe and V oxides supported on N-doped TiO2

Antonietta Mancuso,
Alessandro Gottuso,
Francesco Parrino
et al.

Abstract: Cu, Fe and V oxides supported on N-TiO2 (Cu/N-TiO2, Fe/N-TiO2, and V/N-TiO2) were synthetized by incipient wet impregnation method. The prepared photocatalysts were analyzed by N2 adsorption at -196°C to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In addition, various types of catalysts have also been reported for the direct hydroxylation of benzene to phenol with H 2 O 2 as an oxidant. 13–16 However, the shortcomings of the existing catalyst preparation process, such as high cost or low yield, still exist. In addition, a number of studies have shown that no active oxygen species are generated in the reaction system and the yield of phenol is basically zero without the addition of a catalyst under all conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various types of catalysts have also been reported for the direct hydroxylation of benzene to phenol with H 2 O 2 as an oxidant. 13–16 However, the shortcomings of the existing catalyst preparation process, such as high cost or low yield, still exist. In addition, a number of studies have shown that no active oxygen species are generated in the reaction system and the yield of phenol is basically zero without the addition of a catalyst under all conditions.…”
Section: Introductionmentioning
confidence: 99%